Factors Associated with Intrauterine Fetal Death at Paropakar Maternity Women’s Hospital - Thakur, S.K.; Dangal, G. (Kathmandu University Medical Journal, 2022)
Background Intrauterine fetal death (IUFD) is a demise occurring at 20 or more weeks of gestation and weight 500 gram or more. Intrauterine fetal death at any point during gestation is a traumatic event not only to the patient but also to the care giver. The purpose of this study is to know the risk factors associated with intrauterine fetal death. Objective To determine the factors associated with intrauterine fetal death. Method Prospective observational study was conducted at Paropkar maternity women’s hospital, Thapathali, Kathmandu. All the cases with intrauterine fetal death were admitted and delivered in the hospital with period of gestation 20 weeks to term pregnancy. All the relevant data were recorded in pre-designed proforma. The collected data were entered in SPSS 25 version for analysis. Result There was a total 5153 deliveries in three months, with prevalence of 1.2% and intrauterine rate of 12.03 per 1000 births. Out of 50 enrolled cases, 78% (n=50) of patient had not attended antenatal checkup. Majority (n=50; 74%), belonged to age group 21-35 years, 48% of intrauterine fetal death were term pregnancies of 37 to 42 weeks of gestation. Maximum 20% of IUFD, weighed between (1-1.5 kg) (1.5-2 kg) and (2.5-3 kg). Thirty-nine babies were macerated and eleven non-macerated. Pregnancy induced hypertension was most common (26%), followed by ante-partum hemorrhage (8%), hypothyroidism and anemia (6%), meconium stained liquor and cord prolapse (6%), gestational diabetes mellitus, congenital anomalies, chronic hypertension (4%), intrauterine growth restriction and urinary tract infection (2%). Twelve cases underwent cesarean section. Postpartum complications were found in 10 cases; 4 cases had postpartum hemorrhage, 4 had prolonged hospital stay and 2 cases developed hemolysis, elevated liver enzyme, low platelet count (HELLP) syndrome. Conclusion This study concluded that maximum no. of intrauterine fetal death were seen antenatally, as 78% of cases were found macerated. The commonest identified risk factor was pregnancy induced hypertension, followed by ante-partum hemorrhage, anemia, hypothyroidism, which seem to be preventable risk factors of intrauterine fetal death, but still unidentified risk factors are of great challenges for the obstetricians.